2021
DOI: 10.21203/rs.3.rs-657692/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidative Stress and Cardiometabolic Biomarkers in Patients with Non-alcoholic Fatty Liver Disease

Abstract: Objective: Oxidative stress is assumed to be the underlying feature of non-alcoholic fatty liver disease (NAFLD). To our knowledge, the mutual involvement of redox status homeostasis parameters [i.e., advanced oxidation protein products (AOPP), pro-oxidant-antioxidant balance (PAB), total oxidant status (TOS), total antioxidant status (TAS) and oxidative-stress index (OSI)] and cardiometabolic biomarkers in subjects with NAFLD has not been examined yet. Accordingly, we aimed to investigate this potential relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…From the measurements of blood lipids, Castelli indices 1 and 2 were calculated. 5 The Shapiro-Wilk tests were used to determine whether the distribution between the variables was normal, when non-normality was verified, the data were presented in medians and quartiles. To verify the association between the amount of energy daily used in physical activities performed by women (3DPAR) and the other variables (Age, BMI, blood pressure, total cholesterol, triglycerides, and lipoproteins) the Friedman test was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the measurements of blood lipids, Castelli indices 1 and 2 were calculated. 5 The Shapiro-Wilk tests were used to determine whether the distribution between the variables was normal, when non-normality was verified, the data were presented in medians and quartiles. To verify the association between the amount of energy daily used in physical activities performed by women (3DPAR) and the other variables (Age, BMI, blood pressure, total cholesterol, triglycerides, and lipoproteins) the Friedman test was used.…”
Section: Methodsmentioning
confidence: 99%
“…We can exemplify this from anthropometric tests (such as Body Mass Index -BMI), blood pressure measurements, and even blood tests to check blood lipids and cholesterol-carrying lipoproteins. 4,5 Once diagnosed, the patient will need treatment that may involve the use of one or more drugs and other lifestyle changes (usually exercise and diet).…”
Section: Introductionmentioning
confidence: 99%
“…leptin resistance, which deprives leptin of its protective effects, and insulin resistance develops in these patients. Klisic et al [26,27], trying to connect oxidative stress, inflammation, and dyslipidemia in patients with T2D with fatty liver disease, concluded that only a multimarker approach, including mentioned biomarkers, could be beneficial in predicting the risk of developing this serious comorbidity. The significant relationship between increased xanthine oxidase activity and uric acid concentration with albuminuria progression in T2D patients undoubtedly links oxidative stress exacerbation with kidney disease as a chronic diabetes complication [28].…”
Section: Oxidative Stress and Inflammation In Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…In addition, in an attempt to better explain the complex pathophysiological processes and to find the best predictors of cardiometabolic disorders some recent reports included a variety of biomarkers that reflect different signaling pathways of the mentioned disorders. In line with this, we have recently shown that a statistical approach that included principal component analysis (PCA) of various biomarkers, rather than each biomarker alone, can be a better determinant of some metabolic disorders (15)(16)(17). However, to our knowledge, there are no studies that applied PCA including different oxidative stress, inflammation, and cardiometabolic biomarkers in populations with prediabetes and overt diabetes.…”
Section: Introductionmentioning
confidence: 98%